Stress, Family Support, Coping Strategies in Single Mother Bereaved by Spousal Death - Jasmita, Reni; Juliawati, Dosi; Harmalis, Harmalis (Psyche 165 Journal, 2024)
Prolonged grief, economic difficulties, anxiety about supporting children, problems adjusting to new conditions, feelings of alienation from the environment, and loss of intimate support from close people. From this, the purpose of this study is to determine whether there is an influence between stress and family support on coping strategies. The research method used was quantitative cross sectional survey research. Sampling using total sampling technique. The research subjects were 32 samples with the criteria that single mothers aged 35 to 45 years. The scale used in this study is the Perceived Stress Questionnaire (PSQ) to measure the extent to which situations in an individual's life can be assessed as a perception of stress, Family Support Scale (FSS), Coping Scale (QS) to measure coping strategies and the ability of individuals to adjust to various stressors experienced. The research data were analyzed using multiple regression methods by utilizing the Statistical Package for Social Sciece (SPSS) version 20 program. The results of data analysis show that there is an influence between stress and family support on coping strategies. From the results of hypothesis testing, a significant value is obtained between stress and family support on coping strategies as evidenced by the significant value of (0.000 <0.05) and the value of f count 14.055> from the value of f table 3.33 then Ha is accepted, meaning that there is an influence between stress and family support on coping strategies in single mothers significantly.